Study on Influence of Ultrasonic Vibration Lapping Gear on the Machining Quality of Tooth Flank - Derong Zhu; Xiaozhong Deng; Jianjun Yang (Jixie chuandong)
Two pairs of hypoid gears with 7/37 and 8/41 teeth are selected as experimental objects. The ultrasonic lapping of gear is carried out on the modified rolling inspection machine Y9550， ultrasonic vibration frequency is 16 kHz， ultrasonic grinding time is 3 min. Then the JD45+ measuring machine is used to measure the deviation error of 45 points on the tooth flank before and after ultrasonic lapping， and then the helical angle or pressure angle error are calculated by the tooth flank error in the direction of tooth length or tooth height. Finally， the tooth flank error， spiral angle error and pressure angle error before and after vibration processing are compared. The results show that ultrasonic vibration lapping gear can eliminate gear flank error， improve the position and shape of gear contact area， improve gear tooth flank smoothness， improve gear machining quality， but also can′t be excessively lapping.